IDENTIFICATION OF MESOSCALE CONVECTIVE COMPLEX (MCCS) AT SOUTHERN PAPUA FOR THE PERIOD OF DECEMBER 2017 – NOVEMBER 2022 - Adhitiansyah, Daffa; Veanti, Desak Putu Okta; Sosaidi, Dedi Sucahyono; Fadlan, Ahmad (Indonesian Physical Review, 2023)
One factor contributing to rainfall in a certain region is the presence of convective cloud growth. Extensive convective clouds can trigger extreme weather conditions and the occurrence of Mesoscale Convective Complex (MCC) phenomena. MCCs phenomena are characterized by circular cloud cover with eccentricity ≥ 0.7, core cloud area ≥ 50,000 km², cloud cover area ≥ 100,000 km², and cloud top temperature ≤ -52 °C or 221 K. This study aims to identify the spatial and diurnal of MCC in the Southern Papua and for the period of December 2017 to November 2022, as well as to assess its impacts on rainfall during MCC events. Satellite data from Himawari-8 in IR channel was used to analyze MCCs criteria, which were then plotted using a geographic visualization software. Rainfall data in GSMaP was processed using GrADS to display rainfall values. The data processing procedure is carried out using an algorithm based on the study conducted by Maddox. The results of the spatial distribution analysis showed that there were 20 MCC events that occurred during the 5-year period, with dominant growth in inland areas near mountainous and high-topography regions. Seasonally, MCC events predominantly occurred during the MAM period and were least frequent in the JJA period. The diurnal distribution revealed that MCC events had a nocturnal life cycle, forming during the nighttime until early morning. Analysis of the GSMaP rainfall data indicated that the dominant rainfall intensity caused by MCC events was heavy rain (20 – 50 mm/hr).